Strategic objectives affecting the structure of service innovation partnerships in technology- and knowledge-intensive sectors. (1st January 2011) - Pateli, Adamantia
Pursuing and achieving service innovation is of utmost importance for firms operating in technology- and knowledge-intensive sectors. The lack of market consolidation combined with the environment uncertainty – due to both market volatility and technology unpredictability – require the formation of partnerships to produce innovation in ever-shorter service life cycles. Recent research in partnerships has suggested that some governance structures are inherently more likely than others to be associated with high opportunity to cheat, obtain new competence, adjust to changing environment conditions, and finally expand. The present study merged these theoretical insights into a general model of structuring and tested it with data from 99 strategic partnerships, 65 of which aimed at service innovation, in the Greek information and communication technology market. The empirical findings generally supported the proposed hypotheses, however, suggesting the need for a greater focus on transaction costs and real options arguments in the study of service innovation partnerships.